Comparison of TSH and Free T4 Hormone Levels in Individuals with Glucose-6-Phosphate Dehydrogenase Deficiency and Healthy Individuals - S Roozbahan; MS Karami; MJ Ghasemi; R Arab Solghar; R Shafiei; SM Shafiei (Armaghane Danesh Bimonthly Journal, 2025)
Background & aim: Iodinated thyroid hormones regulate a variety of biochemical reactions in almost all tissues of the body. These hormones are important factors in the regulation of gene expression in tissues such as; Brain, liver, muscle and adipose tissue are known. Numerous studies have shown that thyroid hormones regulate the activity of the G6PD enzyme. Therefore, the aim of the present study was to determine and compare the levels of TSH and free T4 hormones in individuals with glucose-6-phosphate dehydrogenase deficiency and healthy individuals.